Eléments concernant la structure et la dynamique du phytoplancton du littoral roumain de la Mer Noire pendant la période 1972 – 1977 - Bodeanu, Nicolae; Roban, Anca; Ușurelu, Mioara (Cercetări Marine - Recherches Marines, 2026)
The structure and dynamic peculiarities of the phytoplankton from the Romanian Black Sea area are presented in the paper. The problems are discussed in connection with the eutrophication process and the decreasing salinity recorded in different time periods during the 1972-1977. There are also pointed out the important stocks of phytoplankton produced in some characteristic zones.